Impact of introducing electronic acute kidney injury alerts in primary care - Aiyegbusi, Oshorenua (Clin Kidney J, 2018)
BACKGROUND: Acute kidney injury (AKI) is associated with decreased survival, future risk of chronic kidney disease and longer hospital stays. Electronic alerts (e-alerts) for AKI have been introduced in the UK in order to facilitate earlier detection and improve management. The aim of this study was to establish if e-alerts in primary care were acted on by examining timing of repeat creatinine testing. METHODS: The National Health Service England Acute Kidney Injury electronic alert algorithm was introduced in April 2015 across both primary and secondary care in NHS Tayside accompanied by a programme of education. Data from a 12-month period (2012) predating introduction of the e-alerts were compared with a 12-month period following implementation of e-alerts for AKI. Biochemistry testing following the AKI episode, timing of repeat tests and numbers of patients hospitalized within 7 days of episode were compared between the two time periods. RESULTS: During the 12 months after e-alert introduction, 9781 AKI e-alerts were generated. Of these, 1460 (14.9%) alerts were generated in primary care. Median duration to repeat blood testing for these primary care alerts was 5 days for AKI Stage 1 [interquartile range (IQR) 2–10], 2 days for Stage 2 (IQR 1–5) and 1 day (IQR 0–2) for Stage 3. During 2012 (prior to e-alert implementation) 8812 AKI episodes were identified. Of these, 2650 tests (30.1%) were requested by primary care staff. Median duration to repeat creatinine testing was longer: 55 days (IQR 20–142) for Stage 1, 38 days (IQR 15–128) for Stage 2 was and 53 days (IQR 20–137) for Stage 3. More patients had biochemistry tests repeated within 7 days of AKI onset, pre-alert implementation; 252 (9.5%) versus 857 (58.7%) (P < 0.001). Rates of hospitalization within 7 days of AKI increased from 342 (12.9%) pre-implementation to 372 (25.5%) post-implementation (P < 0.001). CONCLUSIONS: Within primary care, e-alert implementation was associated with higher rates of creatinine monitoring, but also higher rates of hospitalization.